module Data.Set.Coequaliser where

Set coequalisers🔗

In their most general form, colimits can be pictured as taking disjoint unions and then “gluing together” some parts. The “gluing together” part of that definition is where coequalisers come in: If you have parallel maps then the coequaliser can be thought of as “ with the images of and identified”.

data Coeq (f g : A → B) : Type (level-of A ⊔ level-of B) where
  inc    : B → Coeq f g
  glue   : ∀ x → inc (f x) ≡ inc (g x)
  squash : is-set (Coeq f g)

The universal property of coequalisers, being a type of colimit, is a mapping-out property: Maps from are maps out of satisfying a certain property. Specifically, for a map if we have then the map factors (uniquely) through inc. The situation can be summarised with the diagram below.

We refer to this unique factoring as Coeq-rec.

  : ∀ {ℓ} {C : Type ℓ} {f g : A → B} ⦃ _ : H-Level C 2 ⦄
  → (h : B → C)
  → (∀ x → h (f x) ≡ h (g x)) → Coeq f g → C
Coeq-rec h h-coeqs (inc x) = h x
Coeq-rec h h-coeqs (glue x i) = h-coeqs x i
Coeq-rec ⦃ cs ⦄ h h-coeqs (squash x y p q i j) =
  hlevel 2 (g x) (g y) (λ i → g (p i)) (λ i → g (q i)) i j
  where g = Coeq-rec ⦃ cs ⦄ h h-coeqs

An alternative phrasing of the desired universal property is precomposition with inc induces an equivalence between the “space of maps which coequalise and ” and the maps In this sense, inc is the universal map which coequalises and

To construct the map above, we used Coeq-elim-prop, which has not yet been defined. It says that, to define a dependent function from Coeq to a family of propositions, it suffices to define how it acts on inc: The path constructions don’t matter.

  : ∀ {ℓ} {f g : A → B} {C : Coeq f g → Type ℓ}
  → (∀ x → is-prop (C x))
  → (∀ x → C (inc x))
  → ∀ x → C x
Coeq-elim-prop cprop cinc (inc x) = cinc x

Since C was assumed to be a family of propositions, we automatically get the necessary coherences for glue and squash.

Coeq-elim-prop {f = f} {g = g} cprop cinc (glue x i) =
  is-prop→pathp (λ i → cprop (glue x i)) (cinc (f x)) (cinc (g x)) i
Coeq-elim-prop cprop cinc (squash x y p q i j) =
  is-prop→squarep (λ i j → cprop (squash x y p q i j))
    (λ i → g x) (λ i → g (p i)) (λ i → g (q i)) (λ i → g y) i j
  where g = Coeq-elim-prop cprop cinc

Since “the space of maps which coequalise and ” is a bit of a mouthful, we introduce an abbreviation: Since a colimit is defined to be a certain universal (co)cone, we call these Coeq-cones.

  coeq-cone : ∀ {ℓ} (f g : A → B) → Type ℓ → Type _
  coeq-cone {B = B} f g C = Σ[ h ∈ (B → C) ] (h ∘ f ≡ h ∘ g)

The universal property of Coeq then says that Coeq-cone is equivalent to the maps and this equivalence is given by inc, the “universal Coequalising map”.

Coeq-univ : ∀ {ℓ} {C : Type ℓ} {f g : A → B} ⦃ _ : H-Level C 2 ⦄
          → is-equiv {A = Coeq f g → C} {B = coeq-cone f g C}
            (λ h → h ∘ inc , λ i z → h (glue z i))
Coeq-univ {C = C} {f = f} {g = g} =
  is-iso→is-equiv (iso cr' (λ x → refl) islinv) where
    cr' : coeq-cone f g C → Coeq f g → C
    cr' (f , f-coeqs) = Coeq-rec f (happly f-coeqs)

    islinv : is-left-inverse cr' (λ h → h ∘ inc , λ i z → h (glue z i))
    islinv f = trivial!


Above, we defined what it means to define a dependent function when is a family of propositions, and what it means to define a non-dependent function Now, we combine the two notions, and allow dependent elimination into families of sets:

Coeq-elim : ∀ {ℓ} {f g : A → B} {C : Coeq f g → Type ℓ}
          → (∀ x → is-set (C x))
          → (ci : ∀ x → C (inc x))
          → (∀ x → PathP (λ i → C (glue x i)) (ci (f x)) (ci (g x)))
          → ∀ x → C x
Coeq-elim cset ci cg (inc x) = ci x
Coeq-elim cset ci cg (glue x i) = cg x i
Coeq-elim cset ci cg (squash x y p q i j) =
  is-set→squarep (λ i j → cset (squash x y p q i j))
    (λ i → g x) (λ i → g (p i)) (λ i → g (q i)) (λ i → g y) i j
  where g = Coeq-elim cset ci cg
Coeq-rec₂ : ∀ {ℓ} {f g : A → B} {f' g' : A' → B'} {C : Type ℓ}
          → is-set C
          → (ci : B → B' → C)
          → (∀ a x → ci (f x) a ≡ ci (g x) a)
          → (∀ a x → ci a (f' x) ≡ ci a (g' x))
          → Coeq f g → Coeq f' g' → C
Coeq-rec₂ cset ci r1 r2 (inc x) (inc y) = ci x y
Coeq-rec₂ cset ci r1 r2 (inc x) (glue y i) = r2 x y i
Coeq-rec₂ cset ci r1 r2 (inc x) (squash y z p q i j) = cset
  (Coeq-rec₂ cset ci r1 r2 (inc x) y)
  (Coeq-rec₂ cset ci r1 r2 (inc x) z)
  (λ j → Coeq-rec₂ cset ci r1 r2 (inc x) (p j))
  (λ j → Coeq-rec₂ cset ci r1 r2 (inc x) (q j))
  i j

Coeq-rec₂ cset ci r1 r2 (glue x i) (inc x₁) = r1 x₁ x i
Coeq-rec₂ {f = f} {g} {f'} {g'} cset ci r1 r2 (glue x i) (glue y j) =
  is-set→squarep (λ i j → cset)
    (λ j → r1 (f' y) x j)
    (λ j → r2 (f x) y j)
    (λ j → r2 (g x) y j)
    (λ j → r1 (g' y) x j)
    i j

Coeq-rec₂ {f = f} {g} {f'} {g'} cset ci r1 r2 (glue x i) (squash y z p q j k) =
  is-hlevel-suc 2 cset
    (go (glue x i) y) (go (glue x i) z)
    (λ j → go (glue x i) (p j))
    (λ j → go (glue x i) (q j))
    (λ i j → exp i j) (λ i j → exp i j)
    i j k
    go = Coeq-rec₂ cset ci r1 r2
    exp : I → I → _
    exp l m = cset
      (go (glue x i) y) (go (glue x i) z)
      (λ j → go (glue x i) (p j))
      (λ j → go (glue x i) (q j))
      l m

Coeq-rec₂ cset ci r1 r2 (squash x y p q i j) z =
  cset (go x z) (go y z) (λ j → go (p j) z) (λ j → go (q j) z) i j
  where go = Coeq-rec₂ cset ci r1 r2

  H-Level-coeq : ∀ {f g : A → B} {n} → H-Level (Coeq f g) (2 + n)
  H-Level-coeq = basic-instance 2 squash


With dependent sums, we can recover quotients as a special case of coequalisers. Observe that, by taking the total space of a relation we obtain two projection maps which have as image all of the possible related elements in By coequalising these projections, we obtain a space where any related objects are identified: The quotient

  tot : ∀ {ℓ} → (A → A → Type ℓ) → Type (level-of A ⊔ ℓ)
  tot {A = A} R = Σ[ x ∈ A ] Σ[ y ∈ A ] R x y

  /-left : ∀ {ℓ} {R : A → A → Type ℓ} → tot R → A
  /-left (x , _ , _) = x

  /-right : ∀ {ℓ} {R : A → A → Type ℓ} → tot R → A
  /-right (_ , x , _) = x

We form the quotient as the aforementioned coequaliser of the two projections from the total space of

_/_ : ∀ {ℓ ℓ'} (A : Type ℓ) (R : A → A → Type ℓ') → Type (ℓ ⊔ ℓ')
A / R = Coeq (/-left {R = R}) /-right

quot : ∀ {ℓ ℓ'} {A : Type ℓ} {R : A → A → Type ℓ'} {x y : A} → R x y
    → Path (A / R) (inc x) (inc y)
quot r = glue (_ , _ , r)

Using Coeq-elim, we can recover the elimination principle for quotients:

Quot-elim : ∀ {ℓ} {B : A / R → Type ℓ}
          → (∀ x → is-set (B x))
          → (f : ∀ x → B (inc x))
          → (∀ x y (r : R x y) → PathP (λ i → B (quot r i)) (f x) (f y))
          → ∀ x → B x
Quot-elim bset f r = Coeq-elim bset f λ { (x , y , w) → r x y w }


The most well-behaved case of quotients is when takes values in propositions, is reflexive, transitive and symmetric (an equivalence relation). In this case, we have that the quotient is effective: The map quot is an equivalence.

record Congruence {ℓ} (A : Type ℓ) ℓ' : Type (ℓ ⊔ lsuc ℓ') where
    _∼_         : A → A → Type ℓ'
    has-is-prop : ∀ x y → is-prop (x ∼ y)
    reflᶜ : ∀ {x} → x ∼ x
    _∙ᶜ_  : ∀ {x y z} → x ∼ y → y ∼ z → x ∼ z
    symᶜ  : ∀ {x y}   → x ∼ y → y ∼ x

  relation = _∼_

  quotient : Type _
  quotient = A / _∼_

We will show this using an encode-decode method. For each we define a type family which represents an equality Importantly, the fibre over will be so that the existence of functions converting between and paths is enough to establish effectivity of the quotient.

    Code : A → quotient → Prop ℓ'
    Code x = Quot-elim
      (λ x → n-Type-is-hlevel 1)
      (λ y → el (x ∼ y) (has-is-prop x y) {- 1 -})
      λ y z r →
        n-ua (prop-ext (has-is-prop _ _) (has-is-prop _ _)
          (λ z → z ∙ᶜ r)
          λ z → z ∙ᶜ (symᶜ r))

We do quotient induction into the type of propositions, which by univalence is a set. Since the fibre over must be that’s what we give for the inc constructor ({- 1 -}, above). For this to respect the quotient, it suffices to show that, given we have which follows from the assumption that is an equivalence relation ({- 2 -}).

    encode : ∀ x y (p : inc x ≡ y) → ∣ Code x y ∣
    encode x y p = subst (λ y → ∣ Code x y ∣) p reflᶜ

    decode : ∀ x y (p : ∣ Code x y ∣) → inc x ≡ y
    decode = elim! λ x y r → quot r

For encode, it suffices to transport the proof that is reflexive along the given proof, and for decoding, we eliminate from the quotient to a proposition. It boils down to establishing that which is what the constructor quot says. Putting this all together, we get a proof that equivalence relations are effective.

  is-effective : ∀ {x y : A} → is-equiv (quot {R = relation})
  is-effective {x = x} {y} =
    prop-ext (has-is-prop x y) (squash _ _) (decode x (inc y)) (encode x (inc y)) .snd

Relation to surjections🔗

As mentioned in the definition of surjection, we can view a cover as expressing a way of gluing together the type by adding paths between the elements of When and are sets, this sounds a lot like a quotient! And, indeed, we can prove that every surjection induces an equivalence between its codomain and a quotient of its domain.

First, we define the kernel pair of a function the congruence on defined to be identity under

  : ∀ {ℓ ℓ'} {A : Type ℓ} {B : Type ℓ'} → is-set B → (A → B)
  → Congruence A ℓ'
Kernel-pair b-set f ._∼_ a b = f a ≡ f b
Kernel-pair b-set f .has-is-prop x y = b-set (f x) (f y)
Kernel-pair b-set f .reflᶜ = refl
Kernel-pair b-set f ._∙ᶜ_  = _∙_
Kernel-pair b-set f .symᶜ  = sym

We can then set about proving that, if is a surjection into a set, then is the quotient of under the kernel pair of

The construction is pretty straightforward: each fibre defines an element If we have another fibre then because

so the function is constant, and factors through the propositional truncation

  g₀ : ∀ {x} → fibre f x → c.quotient
  g₀ (a , p) = inc a

    g₀-const : ∀ {x} (p₁ p₂ : fibre f x) → g₀ p₁ ≡ g₀ p₂
    g₀-const (_ , p) (_ , q) = quot (p ∙ sym q)

  g₁ : ∀ {x} → ∥ fibre f x ∥ → c.quotient
  g₁ f = ∥-∥-rec-set (hlevel 2) g₀ g₀-const f

Since each is inhabited, all of these functions glue together to give a function A simple calculation shows that this function is both injective and surjective; since its codomain is a set, that means it’s an equivalence.

  g' : B → c.quotient
  g' x = g₁ (surj x)

  g'-inj : injective g'
  g'-inj {x} {y} = ∥-∥-elim₂ {P = λ a b → g₁ a ≡ g₁ b → x ≡ y}
    (λ _ _ → fun-is-hlevel 1 (b-set _ _))
    (λ (_ , p) (_ , q) r → sym p ∙ c.effective r ∙ q)
    (surj x) (surj y)

  g'-surj : is-surjective g'
  g'-surj x = do
    (y , p) ← inc-is-surjective x
    pure (f y , ap g₁ (squash (surj (f y)) (inc (y , refl))) ∙ p)